2019
DOI: 10.1515/chem-2019-0105
|View full text |Cite
|
Sign up to set email alerts
|

Various Combinations of Flame Retardants for Poly (vinyl chloride)

Abstract: Various combinations of zinc borate (ZB), alumina trihydrate (ATH) and magnesium hydroxide (MH) were used to retard the flammability of PVC composite. Flame retardancy of samples were investigated with limiting oxygen index (LOI) test. Further testing was achieved to expose the individual and synergistic effects of flame retardant additives on heat stability, Vicat softening temperature, fusion time, microstructure, mechanical and thermal characteristics. Microstructural and thermal analyses were performed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Table 2 shows that Sample 1 has the highest tensile strength. The addition of plasticizer from PET and other flame retardants reduced material tensile strengths [27]. Tensile strength is reduced by 8.16 % when PETPlast1 plasticizer is added to VC-co-VAc copolymer materials, by 14.3 % PETPlast2, and 18.4% sa PETPlast3 plasticizers.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 shows that Sample 1 has the highest tensile strength. The addition of plasticizer from PET and other flame retardants reduced material tensile strengths [27]. Tensile strength is reduced by 8.16 % when PETPlast1 plasticizer is added to VC-co-VAc copolymer materials, by 14.3 % PETPlast2, and 18.4% sa PETPlast3 plasticizers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it can also be a valuable tool for supplementing information about structural changes and the miscibility of polymeric compositions [24][25][26]. Referring to previous literature studies, the introduction of insoluble and inert additives to plasticized PVC, including flame retardants and fillers, may induce different tendencies (both increases and decreases) in PVC-P the thermomechanical stability as assessed by the VST criterion [27][28][29]. The results of the VST measurements are presented in Table 2.…”
Section: Mechanical Performancementioning
confidence: 97%
“…This provided an uniform composite stucture. However, in Figure 4(B) it seems that the nano-sized particles were agglomerated and formation of ZB agglomerates lead formation of weak zones in composite structure [30,31]. Since these zones caused a decrease in tensile strength of the composites, it can be inferred that additive ratio and tensile strength are inversely proportional.…”
Section: Tensile Testmentioning
confidence: 97%
“…SEM photographs obtained after the impact strength test of the composite showed that the mixing process time was sufficient and the particles were homogeneously distributed in the polymer structure. However, it was observed that there was a significant decrease in the impact strength of composites containing 5% ZB additive which can be attributed to agglomeration of particles [30,31].…”
Section: Impact Testmentioning
confidence: 98%